Особливості державної гендерної політики в Україні - Дисюк, Т. М.; Дисюк, Т. М.; Disjuk, Т. (My University, 2012)
The maintenance of the public gender policy in a context of support of the equal political and civil rights of women and men in a society is defi ned, the analysis of supporting of the gender parity in public-administrative sphere of Ukraine is carried out, perspective directions of improvement the mechanism of forming and realisation of the public gender policy in Ukraine are specifi ed.
Дисюк Т. М. Особливості державної гендерної політики в Україні / Т. М. Дисюк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 222-229.
Keywords: державна гендерна політика в Україні; забезпечення рівних політичних і громадянських права жінок і чоловіків; гендерний паритет у державно-управлінській сфері в Україні; механізм формування та реалізації державної гендерної політики в Україні; государственная гендерная политика в Украине; обеспечение равных политических и гражданских прав женщин и мужчин; гендерный паритет в государственно-управленческой сфере в Украине; механизм формирования и реализации государственной гендерной политики в Украине; State gender policy in Ukraine; ensuring equal political and civil rights for women and men; gender parity in public-administrative sphere in Ukraine; the mechanism of formation and implementation of state gender policy in Ukraine